Casting polymer from 250-pound autoclave (1938)
View of two DuPont technicians casting polymer from a 250-pound autoclave during the early stages of nylon production and research at the DuPont Experimental Station in Wilmington, Delaware. During production, a partially-evaporated nylon salt solution was fed into the autoclave and heated to 275 degrees centigrade under a pressure of 275 pounds per square inch in order to precipitate polymerization. Once polymerization occurred, additional water was bled off and the pressure was slowly reduced to atmospheric levels before the polymer was extruded. The technicians visible in the photograph are identified as Carl Searles (left) and Gene Herlihey (right).
Keywords: Employees; Nylon; Polymers; Autoclaves; E.I. du Pont de Nemours & Company. Experimental Station; E.I. du Pont de Nemours & Company; Machinery; Nylon--Testing